2016
DOI: 10.1634/theoncologist.2015-0305
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Support Among Oncology Practitioners in a Regional Cancer Center in the Middle East—Improving a Critical Service for Cancer Care

Abstract: This study examined smoking cessation support (SCS) by oncologists in a Jordanian cancer center and found it to be deficient. Recommendations to improve SCS include improving patient‐provider communication and building providers’ self‐efficacy through continuing education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…A reason for this might be that health care providers ask patients about their current smoking status during the initial visit and thus, they do not ask about it again in the follow‐up visit. The results of the current study are comparable to those reported in the survey of oncology practitioners in the Regional Cancer Center in the Middle East where in the follow‐up visit, only 39.3% of health care providers continue tracking smoking status and 42.1% continue encouraging resistant smokers 33 . Nevertheless, the percentages in this study are way less than the ones in the study conducted among the IASLC members.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A reason for this might be that health care providers ask patients about their current smoking status during the initial visit and thus, they do not ask about it again in the follow‐up visit. The results of the current study are comparable to those reported in the survey of oncology practitioners in the Regional Cancer Center in the Middle East where in the follow‐up visit, only 39.3% of health care providers continue tracking smoking status and 42.1% continue encouraging resistant smokers 33 . Nevertheless, the percentages in this study are way less than the ones in the study conducted among the IASLC members.…”
Section: Discussionsupporting
confidence: 78%
“…Percentages of SCC practices in our study especially referring or treating patients who smoke are much lower than those reported in other studies. For instance, a survey of 254 oncology practitioners in a Regional Cancer Center in the Middle East found that 67% of respondents ask if the patient smokes cigarettes, 65.8% advise smokers to quit, and 47% refer those interested in quitting to smoking cessation clinic 33 . In the survey of 1507 multidisciplinary lung cancer specialists who were members of the IASLC, 90% of respondents ask patients about tobacco use, 81% advise patients to stop tobacco use, and 39% refer or treat them 29 .…”
Section: Discussionmentioning
confidence: 99%